Resource limitation, biodiversity, and competitive effects interact to determine the invasibility of rock pool microcosms - Romanuk, T.N; Kolasa, J (Biological invasions, 2005)
The success of species invasions depends on both the characteristics of the invaded habitat and the traits of the invasive species. At local scales biodiversity may act as a barrier to invasion; however, the mechanism by which biodiversity confers invasion resistance to a community has been the subject of considerable debate. The purpose of this study was to test the hypothesis that productivity and diversity affected the ability of a regionally available species to colonize communities from which it is absent. We hypothesized that the invasibility of rock pool invertebrate communities would increase with increasing nutrients and decrease with increasing diversity. We tested this possibility using naturally invaded outdoor aquatic microcosms. We demonstrated that the invasibility of an experimental multi-trophic aquatic community by a competitive native midge species (Ceratopogonidae: Dasyhelea sp.) was determined by an interaction between resource availability, diversity, and the densities of two competitive ostracods species. Nutrient enrichment increased invasion success; however, within nutrient-enriched microcosms, invasion success was highest in the low-diversity treatments. Our results suggest that resource availability may in fact be the principal mechanism determining invasibility at local scales in multi-trophic rock pool communities; however resource availability can be determined by both nutrient input as well as by the diversity of the biotic community.[PUBLICATION ABSTRACT]